Basic Programs for Chemical Engineers - Wright, Dennis (New York Van Nostrand Reinhold Company, 1986)
This is a really nice piece of work that could help all chemical engineers,especially chemical engineering students..But it could have include much more specific things. As a conclusion this is a great book if you are looking for general programs but it doesn't reach to people who are looking for specific kinds of problems.
Include Tables, Figures, Appendix and Index.
Keywords: BASIC (Computer program language) -- Chemical engineering--Computer programs -- Biotechnology -- Chemical engineering -- Chemistry -- Computer science -- Electronic data processing